(untitled) (Pulse, 2016)
Osteoid osteoma is a benign bone forming tumor of the growing skeleton that is most often seen in young men. It represents by pain and radiologic appearance of a nidus surrounded by osteosclerosis that occurs mostly in long bones of the lower extremity. Occurrence of this tumor in the hand is an uncommon condition. A 35 year old right-hand-dominant man presented to our orthopedic and trauma OPD with an approximately 2 year history of right middle finger pain without any history of trauma. He consulted previously with a local doctor and had undergone xray of the hand with no definitive diagnosis. Computed tomography at our institution was consistent with the diagnosis of osteoid osteoma. The patient was treated with surgical excision of the lesion without bone grafting. The diagnosis of osteoid osteoma was confirmed by histopathology. Follow up visit showed complete resolution of pain. In this case demonstrating that osteoid osteoma is an important differential diagnosis in patients with finger pain. Pulse Vol.8 January-December 2015 p.69-72